A new mutation in the KINDLIN‐3 gene ablates integrin‐dependent leukocyte, platelet, and osteoclast function in a patient with leukocyte adhesion deficiency‐III. Issue 9 (8th April 2015) - Crazzolara, Roman; Maurer, Kathrin; Schulze, Harald; Zieger, Barbara; Zustin, Jozef; Schulz, Ansgar S.
<x xml:space="preserve">Abstract</x> Disabling mutations in integrin‐mediated cell signaling have been a major focus of interest over the last decade for patients affected with leukocyte adhesion deficiency‐III (LAD‐III). In this study, we identified a new C>T point mutation in exon 13 in the FERMT3 gene in an infant diagnosed with LAD‐III and showed that KINDLIN‐3 expression is required for platelet aggregation and leukocyte function, but also osteoclast‐mediated bone resorption. After allogeneic bone marrow transplant, all overt symptoms disappeared. This newly identified mutation along with its novel role in dysregulation of bone homeostasis extends our understanding of KINDLIN‐3 in humans. Pediatr Blood Cancer 2015;62:1677–1679. © 2015 Wiley Periodicals, Inc.